Angular velocity around the longitudinal axis in combination with head movements of springboard divers during twisted somersaults - Natrup, J.; de Lussanet, M. H. E.; Boström, K. J.; Wagner, H. (Sports Biomechanics, 2023)
The ability of springboard divers to perform and control difficult elements with multiple twisted somersaults before entering the water is of great interest for coaches and researchers. In order to produce twists within somersaults, divers use both `contact` and `aerial` techniques. After completing body axes rotations, head movements seem to be important, as they enable visual information in the air. The current study aims at investigating angular velocities around the longitudinal axis in combination with head movements of 13 springboard divers during twisted somersaults. Divers performed forward and backward somersaults with different numbers of half twists. The results revealed maximum longitudinal axis angular velocities between 500°/s and 1300°/s. Moreover, results showed that the use of contact technique was greater in twisted somersaults with backward approaches, and thus higher angular velocities could be achieved. While finishing the twists, head movements in the opposite direction to the longitudinal axis rotation occurred, which allow divers to orient themselves. Twist speeds influenced athletes` head movements to have greater angles and greater rotational velocities. Therefore, it is concluded that fast head movements are necessary in difficult twisted dives to allow orientation in the short phase between finishing the twist and entering the water surface.